The Outcome of Induction Therapy for EBV-Related Hemophagocytic Lymphohistiocytosis: A Model for Risk Stratification - Cui, Tingting; Wang, Jingshi; Wang, Zhao (Frontiers in Immunology, 2022)
Background Epstein–Barr virus (EBV)–related hemophagocytic lymphohistiocytosis (HLH) is an abnormal inflammation caused by EBV infection, which has high mortality during induction therapy. Objectives This study is aimed to build a model to predict the risk of death during induction therapy. Methods The patients with EBV-HLH admitted from January 2015 to December 2018 were retrospectively reviewed. The primary outcome was death during induction therapy. The interval from receiving therapy to death or the end of induction therapy was the observing time. The patients admitted from January 2015 to December 2017 were assigned to the primary group, and the patients admitted from January to December 2018 were assigned to the validation group. Results We included 234 patients with EBV-HLH, of whom 65 (27.4%) died during induction therapy. The middle observing time was 25 days. On the basis of the primary group, the multivariate Cox analysis demonstrated age >18 years, blood urea nitrogen, procalcitonin >2 µg/L, serum CD25, and EBV-DNA in peripheral blood mononuclear cell as the risk factors of death during induction therapy. We developed a nomogram integrating the above factors with high predictive accuracy (c-statistic, 0.86) and stratified all patients into the high-risk and the low-risk groups. On the basis of the validation group, the high-risk patients had a higher risk of death (hazard ratio, 4.93; P = 0.012). In the subgroup analysis based on patients receiving etoposide-based strategy, the mortality in high-risk and low-risk patients was 43.9 and 3.1 per 100 person-weeks, respectively. Conclusion We developed a nomogram for risk stratification of patients with EBV-HLH receiving induction therapy.